System of an assessment of the personal activity efficiency of social establishments: features of development and deployment - O. V. Nikonova (Путеводитель предпринимателя, 2020)
Now for full satisfaction of needs of clients in the social services meeting the modern requirements, there is a modernization and development of system of social service of the population, adaptation to changing legal, social and economic and demographic conditions, including, a solution of personnel problems of branch. Work on development and deployment of system of an assessment of efficiency of activity of the personnel, systematic transition of the personnel of social establishments on «effective contracts» is conducted.